Roman Shakespeare : warriors, wounds, and women - Kahn, Coppélia. (London ; New York : Routledge, 1997)
Annotation The first full-length study of Shakespeare's Roman plays offers fresh, detailed readings and identifies new sources which are analyzed from a historical feminist perspective.
1. Roman virtue on English stages -- 2. The sexual politics of subjectivity in Lucrece -- 3. The daughter's seduction in Titus Andronicus, or, writing is the best revenge -- 4. Mettle and melting spirits in Julius Caesar -- 5. Antony's wound -- 6. Mother of battles : Volumnia and her son in Coriolanus.
Includes bibliographical references (pages 171-184) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Shakespeare, William, -- 1564-1616 -- Knowledge; Shakespeare, William, -- 1564-1616 -- Political and social views; Shakespeare, William, -- 1564-1616; Feminism and literature -- England -- History -- 17th century; Masculinity in literature; Wounds and injuries in literature; English drama -- Roman influences; Sex role in literature; Heroes in literature; Women in literature; Rome -- In literature; Women -- history; Drama -- history; Masculinité dans la littérature.; Lésions et blessures dans la littérature.; Rôle selon le sexe dans la littérature.; Héros dans la littérature.; Femmes dans la littérature.; LITERARY CRITICISM -- Shakespeare; DRAMA -- Shakespeare; English drama -- Roman influences; Feminism and literature; Heroes in literature; Literature; Masculinity in literature; Political and social views; Sex role in literature; Women in literature; Wounds and injuries in literature; England; Rome (Empire); 1600-1699; Electronic books; History